2020
DOI: 10.1017/s1352465820000685
|View full text |Cite
|
Sign up to set email alerts
|

Culturally adapted trauma-focused CBT-based guided self-help (CatCBT GSH) for female victims of domestic violence in Pakistan: feasibility randomized controlled trial

Abstract: Background: Cognitive behaviour therapy (CBT), self-help and guided self-help interventions have been found to be efficacious and cost effective for victims of trauma, but there are limited data from low- and middle-income countries on culturally adapted interventions for trauma. Aims: To investigate the feasibility and acceptability of culturally adapted trauma-focused CBT-based guided self-help (CatCBT GSH) for female victims of domestic violence in Pakistan. Method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…A systematic review was conducted in which eight articles were selected to assess the current empirical evidence of CBT for the treatment of psychological harm in domestically abused women. To begin with, based on the articles selected according to the inclusion and exclusion criteria, the majority of publications have been conducted at the international level (87.5%) (Andersson et al, 2021;Graham-Bermann et al, 2019;Greene et al, 2019;Johnson et al, 2020;Latif et al, 2021;Orang et al, 2018;Osma et al, 2022), compared to the regional (12.5%) (Habigzang et al, 2018); however, at the national level, no studies addressing the proposed topic were found in the databases consulted up to the date of review. Possibly the absence of research in Ecuador on CBT in DV may be attributable to multiple factors such as the lack of funding (governmental or private) for intervention projects, the inexistence of a governing body that regulates the practice of psychotherapists (Guano & Costales, 2021) complete, or pay for a treatment, which will make it difficult to establish processes for research purposes.…”
Section: Resultados Y Discussionmentioning
confidence: 99%
“…A systematic review was conducted in which eight articles were selected to assess the current empirical evidence of CBT for the treatment of psychological harm in domestically abused women. To begin with, based on the articles selected according to the inclusion and exclusion criteria, the majority of publications have been conducted at the international level (87.5%) (Andersson et al, 2021;Graham-Bermann et al, 2019;Greene et al, 2019;Johnson et al, 2020;Latif et al, 2021;Orang et al, 2018;Osma et al, 2022), compared to the regional (12.5%) (Habigzang et al, 2018); however, at the national level, no studies addressing the proposed topic were found in the databases consulted up to the date of review. Possibly the absence of research in Ecuador on CBT in DV may be attributable to multiple factors such as the lack of funding (governmental or private) for intervention projects, the inexistence of a governing body that regulates the practice of psychotherapists (Guano & Costales, 2021) complete, or pay for a treatment, which will make it difficult to establish processes for research purposes.…”
Section: Resultados Y Discussionmentioning
confidence: 99%
“…A considerable degree of heterogeneity was observed, especially among PTSD effect sizes, potentially suggesting that caution should be applied when interpreting the summary effects, (Deeks et al, 2011) One outlier (demonstrating a much stronger effect of TF-GSH) was identified in each meta-analysis (Latif et al, 2021;Sloan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several outliers (Latif et al, 2021;Sloan et al, 2012) were identified (see Figure 2). See Figure S2 F I G U R E 1 Preferred reporting items for reviews and meta-analysis flow chart of study selection process Removing the Latif et al (Latif et al, 2021) depressive symptoms effect size reduced the strength of the effect of TF-GSH on depressive symptoms by g = 0.17 and almost eliminated heterogeneity among depressive symptom effect sizes (reducing τ 2 by 0.44). A moderate effect favouring TF-GSH was observed for depressive symptoms (k = 12, g = −0.56, 95% CI: −0.78, −0.33), with a small degree of heterogeneity among effect sizes (Q (11) = 27.14, p < .01, τ 2 = 0.09, I 2 = 58%).…”
Section: Moderator Analyses and Risk Of Biasmentioning
confidence: 99%
See 2 more Smart Citations